2021
DOI: 10.2147/copd.s339243
|View full text |Cite
|
Sign up to set email alerts
|

Serum Creatinine/Cystatin C Ratio Associated with Cross-Sectional Area of Erector Spinae Muscles and Pulmonary Function in Patients with Chronic Obstructive Pulmonary Disease

Abstract: Purpose Muscle atrophy is a major clinical feature of chronic obstructive pulmonary disease (COPD) and is considered a predictor of mortality in COPD patients. Recently, the cross-sectional area (CSA) of the erector spinae muscles measured by chest computed tomography (CT) scans (ESM CSA ) has been reported as a clinical parameter reflecting disease severity and future prognosis in patients with COPD. In addition, the serum creatinine (Cr)/cystatin C (CysC) ratio has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…Oxidative stress in lung tissue and accumulation of excess protease are both important factors that cause pulmonary inflammatory response and damage in COPD patients [ 25 ]. CysC is a major extracellular cathepsin inhibitor, which has been confirmed as an inflammatory marker of acute exacerbation [ 26 ]. CysC is absorbed and metabolized by renal tubules after glomerular filtration, and the kidney is the only organ to remove CysC.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress in lung tissue and accumulation of excess protease are both important factors that cause pulmonary inflammatory response and damage in COPD patients [ 25 ]. CysC is a major extracellular cathepsin inhibitor, which has been confirmed as an inflammatory marker of acute exacerbation [ 26 ]. CysC is absorbed and metabolized by renal tubules after glomerular filtration, and the kidney is the only organ to remove CysC.…”
Section: Discussionmentioning
confidence: 99%
“…As expected, LAA% was significantly higher in association with impairment of pulmonary function. BMI, ESM CSA , and Cr/CysC ratio, which is an indicator of sarcopenia in COPD patients, 28–30 were decreased in patients with severe COPD compared with smoker controls. HsCRP levels were significantly increased in patients with severe COPD compared with smoker controls and patients with moderate and mild COPD ( Table 1 ).…”
Section: Resultsmentioning
confidence: 91%
“…LAA% was measured as previously reported. 25 , 27 , 28 Briefly, high-resolution computed tomography (CT) scans were acquired using a 128-multidetector CT scanner (Somatom Definition FLASH; Siemens Medical Solutions, Erlangen, Germany) with a slice thickness of 2 mm. LAA% was calculated using a threshold of −960 Hounsfield units (HU) to assess emphysematous changes and total lung volume using the computer software LungVision TM , version 2.1 (Cybernet Systems Co., Ltd., Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, we did not compare BIA to all skeletal muscles at the level of T12, which is also used as a measure of muscle mass. However, the ESA was selected because it is easily measurable ( 22 ) and is required for locomotion ( 37 ) and previous studies have demonstrated its application ( 9 , 38 , 39 ). Second, data were collected retrospectively, with the variables regarding the muscle strength or physical performance being unavailable.…”
Section: Discussionmentioning
confidence: 99%